Calculating ambient aerosol surface area concentrations using aerosol light scattering enhancement measurements. (1st November 2019) - Kuang, Ye; Tao, JiangChuan; Xu, WanYun; Yu, YingLi; Zhao, Gang; Shen, ChuanYang; Bian, YuXuan; Zhao, ChunSheng
Abstract: Aerosol surface area concentration ( S A ) is crucial for studying atmospheric chemical reactions happened in aerosol water or on aerosol surface. However, there is no commercial instrument that can provide direct measurements of ambient S A . In this paper, we propose a method to calculate ambient S A based only on measurements of a three-wavelength humidified nephelometer system, which measures aerosol optical properties at three wavelengths under dry state and different relative humidity (RH) conditions. Two critical steps are required in this method: (1) Calculating surface area concentration of ambient aerosols in dry state, S A ( dry ), using a trained random forest machine learning model based only on optical properties measured by the "dry" nephelometer. The proposed machine learning method is evaluated with particle number size distributions (PNSD) datasets from eight field campaigns conducted on the North China Plain during different seasons. The square of correlation coefficients between predicted and calculated S A ( dry ) for PNSD is about 0.99, the average ratio between predicted and calculated S A ( dry ) is 1.01 and 70% of data points has a relative difference less than 10%. (2) Calculating the surface area growth factor f S ( RH ) of ambient aerosol particles due to water uptake using the proposed f S ( RH ) parameterization scheme f S ( RH ) = ( 1 + κ S R H 100 − R H ) 2 3, and the hygroscopicity parameter κ S can be calculated using measured aerosol light scattering enhancement factor and Å ngstr o ¨ m exponent. The ambient S A values during two field campaigns which are conducted on the North China Plain (Wangdu campaign and Gucheng campaign, in summer and winter respectively) are calculated using the proposed method. The ambient S A ranges from 42 to 1871 μ m 2 / c m 3 with an average of 319 μ m 2 / c m 3 during Wangdu campaign, and ranges from 19 to 4156 μ m 2 / c m 3 with an average of 788 μ m 2 / c m 3 during Gucheng campaign. Drastic daily variations of ambient S A are observed during these two campaigns. The results demonstrate that aerosol hygroscopic growth impacts significantly on variations in ambient S A especially under high RH conditions. The f S ( RH ) ranges from near 1 to 4 with an average of 1.4 during Wangdu campaign, and ranges from near 1 to 2.7 with an average of 1.3 during Gucheng campaign. The results indicate that the larger RH, the more sensitive f S ( RH ) becomes to variations in κ S which highlights that real-time measurements of aerosol hygroscopicity are required for accurate calculations of ambient S A . The advantage of the proposed method is that the ambient S A can be obtained solely based on measurements of a three-wavelength humidified nephelometer system, facilitating real-time measurements of ambient S A and promoting studies in aerosol heterogeneous reactions. Highlights: Humidified nephelometer system performs great in predicting aerosol surface area. Proposed method can be used in different regions. Aerosol hygroscopic growth impacts significantly on aerosol surface area.